2016
DOI: 10.1071/an15489
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and genomic relationship between methane production measured in breath and fatty acid content in milk samples from Danish Holsteins

Abstract: Abstract. In this study the objective was to estimate the genetic and genomic relationship between methane-related traits and milk fatty acid profiles. This was done using two different estimation procedures: a single nucleotide polymorphismbased genomic relationship matrix and a classical pedigree-based relationship matrix. Data was generated on three Danish Holstein herds and a total of 339 cows were available for the study. Methane phenotypes were generated in milking robots during milking over a weekly per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
(27 reference statements)
2
5
1
1
Order By: Relevance
“…Within-week methane measurements had a high repeatability coefficient of 0.70 ± 0.02 (estimate ± SE). Estimated average daily methane emission was 395.8 ± 63.5 g/d (mean ± SD), which was consistent with reports from the literature[ 16 ]. Considerable variation in estimated CH 4 emission among cows was observed.…”
Section: Resultssupporting
confidence: 89%
“…Within-week methane measurements had a high repeatability coefficient of 0.70 ± 0.02 (estimate ± SE). Estimated average daily methane emission was 395.8 ± 63.5 g/d (mean ± SD), which was consistent with reports from the literature[ 16 ]. Considerable variation in estimated CH 4 emission among cows was observed.…”
Section: Resultssupporting
confidence: 89%
“…These estimated heritabilities of DMI1 and DMI3 were within the range (0.11 to 0.35) of previous studies presenting heritabilities (Veerkamp, 1998;Veerkamp and Thompson, 1999;Berry et al, 2007;Vallimont et al, 2010Vallimont et al, , 2011Williams et al, 2011;Spurlock et al, 2012). Estimated heritabilities of FPCM in the current study were slightly lower than previously reported heritabilities ranging between 0.27 and 0.47 (Van Arendonk et al, 1991;Veerkamp et al, 2012;Pszczola et al, 2013;Lassen et al, 2016); however, the repeatabilities were high (between 0.63 and 0.66; Table 4), meaning that a big portion of the variance was explained by the permanent environmental instead of the genetic variance. Estimated heritabilities for LW in the current study were in the range of estimates in the literature ranging from 0.43 to 0.65 (Veerkamp and Brotherstone, 1997;Koenen and Veerkamp, 1998;Berry et al, 2003;Muller et al, 2006;Dechow et al, 2010).…”
Section: Estimated Genetic Parameterssupporting
confidence: 78%
“… 67 , Lassen et al . 68 and Wilson et al . 69 performed genomic prediction type analyses while searching for correlated traits.…”
Section: Discussionmentioning
confidence: 94%